Interleukin-27 and Its Diverse Effects on Bacterial Infections - Morita, Yugo; Masters, Elysia A.; Schwarz, Edward M.; Muthukrishnan, Gowrishankar (Frontiers in Immunology, 2021)
Innate and adaptive immune responses against pathogens are known to be carefully orchestrated by specific cytokines that initiate and down regulate immune cell functions from the initial infection through tissue repair and homeostasis. However, some cytokines, including interleukin-27, are expressed at multiple phases of the infection, such that their pro and anti-inflammatory functions have been difficult to interpret. As elucidation of specific cytokine functions throughout infection is central to our understanding of protective vs. susceptible immunity and return to homeostasis vs. prolonged inflammation leading to septic shock, here we review the literature on IL-27 signaling and the various functions of this heterodimeric ligand member of the IL-12 cytokine family. Canonically, IL-27 is produced by antigen-presenting cells, and is thought of as an immunostimulatory cytokine due to its capacity to induce Th1 differentiation. However, many studies have also identified various immunosuppressive effects of IL-27 signaling, including suppression of Th17 differentiation and induction of co-inhibitory receptors on T cells. Thus, the exact role of IL-27 in the context of infectious diseases remains a topic of debate and active research. Additionally, as recent interest has focused on clinical management of acute vs. chronic infections, and life-threatening “cytokine storm” from sepsis, we propose a hypothetical model to explain the biphasic role of IL-27 during the early and late phases of immune responses to reconcile its known pro and anti-inflammatory functions, which could be therapeutically regulated to improve patient outcomes of infection.